Նոր Ջուղայի եկեղեցական ճարտարապետությունն ու գեղարվեստական ժառանգությունը - Արիս Շահդարյան (ՀՀ ԳԱԱ հրատ.)
Армяне поселились в Новой Джульфе вначале XVII века. С 1640 года Джульфа пользовалась репутацией культурного центра. Строились здания и прекрасные церкви с богатой архитектурой, тринадцать из которых стоят до сих пор. Помимо архитектурных композиционных особенностей, внутреннее убранство церкви привлекает взор роскошными фресками и цветочными узорами. Своим архитектурным стилем и великолепными фресками особое место в Новой Джульфе занимает храм Св. Спасителя, построенного в 1655 году.Armenians settled in New Julfa from the beginning of the XVII century. In 1640 Julfa turned into a cultural center with high reputation. Here were built a number of buildings representing rich architecture, such as dwellings and wonderful churches – thirteen of them are standing today. Apart from the architectural compositional features, the interiors of the churches are full of luxurious frescoes and flower-shaped ornaments. In Julfa, the Holy Savior Cathedral built in 1655 is distinguished with its special role, with its architectural style and magnificent frescoes.
Keywords: Christianity; Armenian church; Fine Arts; Architecture